Behavior policy learning: Learning multi-stage tasks via solution sketches and model-based controllers - Tsinganos, Konstantinos; Chatzilygeroudis, Konstantinos; Hadjivelichkov, Denis; Komninos, Theodoros; Dermatas, Evangelos; Kanoulas, Dimitrios (Frontiers in Robotics and AI, 2022)
Multi-stage tasks are a challenge for reinforcement learning methods, and require either specific task knowledge (e.g., task segmentation) or big amount of interaction times to be learned. In this paper, we propose Behavior Policy Learning (BPL) that effectively combines (a) only few solution sketches, that is demonstrations without the actions, but only the states, (b) model-based controllers, and (c) simulations to effectively solve multi-stage tasks without strong knowledge about the underlying task. Our main intuition is that solution sketches alone can provide strong data for learning a high-level trajectory by imitation, and model-based controllers can be used to follow this trajectory (we call it behavior) effectively. Finally, we utilize robotic simulations to further improve the policy and make it robust in a Sim2Real style. We evaluate our method in simulation with a robotic manipulator that has to perform two tasks with variations: (a) grasp a box and place it in a basket, and (b) re-place a book on a different level within a bookcase. We also validate the Sim2Real capabilities of our method by performing real-world experiments and realistic simulated experiments where the objects are tracked through an RGB-D camera for the first task.